Obesitas Sebagai Faktor Risiko Terjadinya Hipertensi Pada Karyawan Universitas Gadjah Mada Yogyakarta - , SURYANINGTYAS DWI SETIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Obesity is one of Cardiovascular diseaseâs risk factor, the famous one is hypertension. Hypertension can be more dangerious disease like stroke and heart disease. Objective: The purpose of this research is to known how big Universitas Gadjah Madaâs employees is suffered with hypertension in one last year influenced obesity as risk factor, and to known the oher risk factor related with hypertension. Method: This research use observational study with cohort prospective historical design. Location of this research is on Universitas Gadjah Mada Yogyakarta. This research is done during September- oktober 2013 with total followers 130 people responden. Result: The result from this research is obesity more risky 4 time to be hypertension than non-obesity group, meanwhile the other risk factor is sex, food (more meat, carbo, vegetable, fruit, milk, coffe), smoking, age when start smoked, physical activities and history of hypertension and Diabetes Mellitus Conclusion : Obesity group have relative risk 4 time biger than non-obesity group to be hypertension.